Antiphospholipids Syndrome Complicated by a Systemic Capillary Leak-Like Syndrome Treated With Steroids and Intravenous Immunoglobulins: A Case Report. Issue 5 (February 2016) - Prete, Marcella; Urso, Livio; Fatone, Maria Celeste; Pinto, Vincenzo; Perosa, Federico
Abstract : Abstract: This report describes the onset of systemic capillary leak (SCL)-like syndrome in a 30-year-old woman with antiphospholipids syndrome (APS) during puerperium. Twelve hours after a cesarean section, she presented a sudden fever and abdominal pains followed by dyspnea, severe edema of the limbs and pelvis. Computer tomography shows congestion of interstitial pulmonary parenchyma, pericardial and pleural effusion, edema of intestinal wall and of perivisceral adipose tissue, and periportal lymphedema. Laboratory tests showed neutrophilic leukocytosis, hypoalbuminemia, and an increase of erythrocyte sedimentation rate and C-reactive protein. Because fever and raised inflammation parameters are not observed in idiopathic capillary leak syndrome (SCLS; Clarkson disease), a diagnosis of SCL-like syndrome was made. Albumin solution, high-dose methylprednisolone and intravenous immunoglobulins (IVIG) infusion were administered with a rapid improvement of her clinical condition. The prompt treatment with steroids and IVIG likely prevented the life-threatening shock syndrome that can occur in SCLS, with acute hypotensive attacks, and severe limbs edema requiring fasciotomy. All clinical and laboratory findings supported autoinflammation as the underlying pathogenic mechanism of the syndrome. The data indicate that SCL-like syndrome can be considered a novel clinical syndrome, which can complicate APS.